Targeted therapy in age-related macular degeneration (AMD) - Szumna, Klaudia Daria; Piędel, Faustyna; Rocka, Agata Agnieszka; Madras, Dominika Katarzyna; Jasielski, Patryk Piotr (Journal of Education, Health and Sport, 2020)
Introduction and purpose: Age-related macular degeneration (AMD) is a major cause of blindness in highly developed countries, with blindness frequency of 8.7%. This article is a review of the latest therapeutic options for AMD. A brief description of the state of knowledge: AMD is a multifactorial disease which etiology is not completely understood. Its development is affected by disorders at the cellular level, environmental and genetic factors. Intraocular injections of anti-VEGF agents are currently considered as the basis of AMD neovascular treatment. In the search for better and better therapeutic agents, the effects of administration of bevacizumab and ranizumab were tested. Many clinical studies confirm long-term and effective improvement in patients' vision after using the above-mentioned drugs, indicating that the initial response to treatment and the persistence of the therapeutic effect is individually variable and may be associated with genotypic difference. Another promising alternative to AMD treatment is the use of specific viral vectors that transfer substances slowing down the disease into the vitreous. Another method of gene therapy is the use of HIF transcription factors (hypoxia-induced factors), for now, the research is performed on animal models. Patients with dry AMD also have a chance for successful treatment. Examined gene therapy in dry form of AMD, including retinal surgery combined with viral vector injection, is in I/II phase study in Great Britain. Conclusions: Looking at the number of blindness cases in highly developed countries caused by AMD, every effort should be made to introduce effective treatment that at least inhibits disease progression. Undoubtedly, more research is needed to confirm the efficacy and long-term safety of AMD.